An ageing anachronism: D.F. Malan as Prime Minister, 1948-1954 - Koorts, Lindie (Kronos: Southern African Histories, 2017)
This article tells the behind-the-scenes tale of the first apartheid Cabinet under Dr D.F. Malan. Based on the utilisation of prominent Nationalists' private documents, it traces an ageing Malan's response to a changing international context, the challenge to his leadership by a younger generation of Afrikaner nationalists and the early, haphazard implementation of the apartheid policy. In order to safeguard South Africa against sanctions by an increasingly hostile United Nations, Malan sought Americas friendship by participating in the Korean War and British protection in the Security Council by maintaining South Africa's Commonwealth membership. In the face of decolonisation, Malan sought to uphold the Commonwealth as the preserve of white-ruled states. This not only caused an outcry in Britain, but it also brought about a backlash within his own party. The National Party's republican wing, led by J.G. Strijdom, was adamant that South Africa should be a republic outside the Commonwealth. This led to numerous clashes in the Cabinet and parliamentary caucus. Malan and his Cabinets energies were consumed by these internecine battles. The systematisation of the apartheid policy and the coordination of its implementation received little attention. Malan's disengaged leadership style implies that he knew little of the inner workings of the various government departments for which he, as Prime Minister, was ultimately responsible. The Cabinet's internal disputes about South Africa's constitutional status and the removal of the Coloured franchise ultimately served as lightning conductors for a larger issue: the battle for the partys leadership, which came to a head in 1954. Malan sought to secure the succession for his favourite, N.C. Havenga. However, he was outmanoeuvred by J.G. Strijdom and his allies. Malan's retirement marked the end of an era, while Strijdom's victory heralded a regional and generational shift in power.